(untitled) (Eurasian Journal of Ecology, 2016)
This article consider the dynamics the main indicators of the natural movement of the population of Kazakhstan during the years of independence. The changes in the population according to the census in the Republic of Kazakhstan. The indicators of infant mortality - one of the basic statistics of the demographic situation in the country.